Penerapan Pendekatan Cooperative Learning Tipe Think Pair Share (TPS) Berbantuan Media Pembelajaran Interaktif Menggunakan Aplikasi Educandy Untuk Meningkatkan Kemampuan Pemahaman Konsep Siswa Kelas 3 Pada Pelajaran Matematika - Rismayanti, Rismayanti; Rahayu, Puji; Putri, Hafidziani Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by the problem of students' low understanding of concepts in Mathematics learning at SD Purwakarta. Therefore, in this study, the application of the Think Pair Share (TPS) cooperative learning approach was carried out with the help of interactive media using the educandy application. The purpose of this study was to find out how the activities and students' conceptual understanding skills when applying the Think Pair Share (TPS) cooperative learning approach assisted by educandy interactive media. The type of research used was Classroom Action Research (PTK) which was conducted in 2 cycles, each cycle was held in 2 meetings. The research subjects were 20 class III students. The research instrument was an observation sheet and test results for students' conceptual understanding abilities. In cycle I the average score reached 62.6 with a percentage of achieving KKM of 60%, in cycle II it increased with an average score of 86.8 with a percentage of achievement of KKM of 90%. Student activity in cycle I reached an average of 3.8 in the good category, in cycle II it increased with an average of 4.0 in the very good category. The conclusions of this study are 1) Learning using the cooperative learning approach of the TPS type assisted by interactive learning media using the educandy application can improve students' conceptual understanding abilities; 2) Learning by applying the TPS-type cooperative learning approach assisted by interactive learning media using the educandy application has an influence on students' conceptual understanding abilities.